2017
DOI: 10.1038/s41598-017-03227-5
|View full text |Cite
|
Sign up to set email alerts
|

APOE gene polymorphism in long-lived individuals from a central China population

Abstract: Previous studies from European and East Asian cohorts reported conflicting results over whether and how the frequencies of the three common alleles, ε2, ε3 and ε4, of the apolioprotein E gene (APOE), in long-lived individuals differ from those in younger age groups. This study was the first to analyse these frequencies of long-lived individuals from central China. Genotyping of APOE alleles and genotypes was carried out in 70 long-lived individuals and 204 younger controls. No difference in the frequency of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Genetic variation in APOE is well known to be associated with longevity and lifespan, with the first report more than two decades ago in a small candidate gene study 27 . Since then, there have been numerous candidate gene studies, including individuals of diverse ancestry, which have identified associations of ApoE with longevity 2832 . However, thus far, rs7412, the ApoE ε2-defining, genetic variant has not been reported to show a genome-wide significant association in GWA studies of longevity and lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation in APOE is well known to be associated with longevity and lifespan, with the first report more than two decades ago in a small candidate gene study 27 . Since then, there have been numerous candidate gene studies, including individuals of diverse ancestry, which have identified associations of ApoE with longevity 2832 . However, thus far, rs7412, the ApoE ε2-defining, genetic variant has not been reported to show a genome-wide significant association in GWA studies of longevity and lifespan.…”
Section: Discussionmentioning
confidence: 99%